Avaliação do temperamento em Bovinos de Corte - NAARA GIOVANNA MELO RANGEL (2024)
The work aims to present bovine temperament, deals with its definition and associations with production characteristics, and includes the discussion of some selection criteria related to Animal Improvement programs.